PROSES PEMASUNGAN PADA PASIEN GANGGUAN JIWA - Dhita Kurnia Sari (GLOBAL HEALTH SCIENCE, 2017)
Physical restraint and confinement of the mentally ill patient (called pasung in Indonesia) are still common problem in Indonesia. Earlier survey showed that from two of three family said that pasung process not only supported by family member but also motivated by civilization including neighbourhood. Although pasung obviously breaking the laws in UU Kesehatan Jiwa Pasal 70 No. 18 tahun 2014 about patient right in mental ill. These research main goals was to described about pasung process in mental ill patient. Design used was qualitative with approachment method fenomenology interpretative. In-depth interview using semistructural questions involved 6 family with mental illness patient in Puskesmas Kras area. Data collected and analyzed using tematik analysis with Braun and Clarke approachment. These research showed 7 theme there are environment, family that depressed, perspective pasung in family, stress in family, family discussion, pasung process and caring modification. The interview results was from all the pasung process started with environment and family that treager family who has stress. And then family discussing with all the member to solved the patient problem. After being pasung, the family modified the treatment to recurring the patient. When modification did not worked, then pasung will be started all over again. These decision affected by environment. Keyword: Pasung process, Mental disorder